Immune Resolution Dilemma: Host Antimicrobial Factor S100A8/A9 Modulates Inflammatory Collateral Tissue Damage During Disseminated Fungal Peritonitis - Shankar, Madhu; Uwamahoro, Nathalie; Backman, Emelie; Holmberg, Sandra; Niemiec, Maria Joanna; Roth, Johannes; Vogl, Thomas; Urban, Constantin F. (Frontiers in Immunology, 2021)
Intra-abdominal infection (peritonitis) is a leading cause of severe disease in surgical intensive care units, as over 70 % of patients diagnosed with peritonitis develop septic shock. A critical role of the immune system is to return to homeostasis after combating infection. S100A8/A9 (calprotectin) is an antimicrobial and pro-inflammatory protein complex used as a biomarker for diagnosis of numerous inflammatory disorders. Here we describe the role of S100A8/A9 in inflammatory collateral tissue damage (ICTD). Using a mouse model of disseminated intra-abdominal candidiasis (IAC) in wild-type and S100A8/A9-deficient mice in the presence or absence of S100A9 inhibitor paquinimod, the role of S100A8/A9 during ICTD and fungal clearance were investigated. S100A8/A9-deficient mice developed less ICTD than wild-type mice. Restoration of S100A8/A9 in knockout mice by injection of recombinant protein resulted in increased ICTD and fungal clearance comparable to wild-type levels. Treatment with paquinimod abolished ICTD and S100A9-deficient mice showed increased survival compared to wild-type littermates. The data indicates that S100A8/A9 controls ICTD levels and antimicrobial activity during IAC and that targeting of S100A8/A9 could serve as promising adjunct therapy against this challenging disease.